2011
DOI: 10.1186/cc10142
|View full text |Cite
|
Sign up to set email alerts
|

Age of red blood cells and mortality in the critically ill

Abstract: IntroductionIn critically ill patients, it is uncertain whether exposure to older red blood cells (RBCs) may contribute to mortality. We therefore aimed to evaluate the association between the age of RBCs and outcome in a large unselected cohort of critically ill patients in Australia and New Zealand. We hypothesized that exposure to even a single unit of older RBCs may be associated with an increased risk of death.MethodsWe conducted a prospective, multicenter observational study in 47 ICUs during a 5-week pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
90
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 33 publications
6
90
0
1
Order By: Relevance
“…1 page 667 Concern was heightened when a large observational study of cardiac surgery patients found an increased risk of postoperative complications and reduced survival in those who received RBCs stored for more than 14 days. 2 Although still controversial, adverse clinical consequences have since been reported in most, [3][4][5] although not all, 6,7 epidemiologic studies of transfusions of RBCs stored for longer durations, but still within Food and Drug Administration (FDA) guidelines. The association between the duration of RBC storage and increased rates of serious infections, sepsis, and mortality is particularly strong in trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…1 page 667 Concern was heightened when a large observational study of cardiac surgery patients found an increased risk of postoperative complications and reduced survival in those who received RBCs stored for more than 14 days. 2 Although still controversial, adverse clinical consequences have since been reported in most, [3][4][5] although not all, 6,7 epidemiologic studies of transfusions of RBCs stored for longer durations, but still within Food and Drug Administration (FDA) guidelines. The association between the duration of RBC storage and increased rates of serious infections, sepsis, and mortality is particularly strong in trauma patients.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several retrospective studies have shown increased mortality, higher risk of infections, and multiorgan failure in certain patient populations transfused with older blood, although these studies had various limitations that have been extensively reviewed elsewhere. [2][3][4] To gain better clinical evidence on whether the length of RBC storage affects morbidity and mortality, several randomized clinical trials have been initiated. These include the National Heart, Lung, and Blood Institute (NHLBI) Red Cell Storage Duration Study (RECESS) comparing the effects of fresher RBC units (Յ 10 days of storage) with older RBC units (Ն 21 days of storage) in 1800 cardiac surgery patients; the Cleveland Clinic's Red Cell Storage Duration and Outcomes in Cardiac Surgery comparing postoperative morbid outcomes in recipients (N ϭ 2800) of fresher (Ͻ 14 days) compared with older (Ͼ 20 days) RBCs; the Research Age of Blood Evaluation (ABLE) study being undertaken by the Canadian Institutes of Health comparing the effects of fresher RBC units (Ͻ 8 days of storage) with standard-issue RBC units (2-42 days of storage) in 2500 critically ill patients; and the Age of Red Blood Cells in Premature Infants (ARIPI) trial comparing fresher RBC units (Ͻ 7 days of storage) with standard-issue RBC units (Ͻ 42 days) in 450 low-birth-weight infants.…”
Section: Introductionmentioning
confidence: 99%
“…In a multicentre observational study of 757 ICU patients, an increase in mortality was observed for patients who were transfused with older blood. 40 The age of blood evaluation (ABLE) study is a double-blind, multicentre, parallel randomized controlled clinical trial of 2510 critically ill adults that is currently underway in 3 countries (Canada, France, United Kingdom) to test if transfusion with RBCs stored for 7 days or less is associated with lower 90-day mortality than transfusion with standard-issue RBCs (2-42 days of storage). 41 If a difference is found, the results of the ABLE study will be applicable to critically ill adults but not to other patients.…”
Section: Discussionmentioning
confidence: 99%